Isolation and structure elucidation of main compound originated from sponge Axynissa aplysinoides - Sumaryono, Wahono; Wibowo, Agung Eru; ., Chaidir (INDONESIAN JOURNAL OF PHARMACY, 2005)
Isolation of the main compound of sponge Axynissa aplysinoides collected from Lombok seawater, has been conducted. Methanol extract of dried sponge was fractionated into nonpolar, semipolar and polar fractions using hexane, ethyl acetate and buthanol. Identification and final purification of the main compound was done using column chromatography and high performance liquid chromatography (HPLC). Structure elucidation of the main compound was performed using mass spectrometry (EIMS), 1H- and 13C-NMR spectroscopies. The main compound was identified as (E)-(4-hydroxystyryl) trimethylammonium.Key words : isolation, structure elucidation, Axynissa aplysinoides